The functional organization of human epileptic hippocampus - Klimes, Petr; Duque, Juliano J; Brinkmann, Ben; Van Gompel, Jamie; Stead, Matt; St Louis, Erik K; Halamek, Josef; Jurak, Pavel; Worrell, Gregory (Journal of neurophysiology, 2016)
The function and connectivity of human brain is disrupted in epilepsy. We previously reported that the region of epileptic brain generating focal seizures, i.e., the seizure onset zone (SOZ), is functionally isolated from surrounding brain regions in focal neocortical epilepsy. The modulatory effect of behavioral state on the spatial and spectral scales over which the reduced functional connectivity occurs, however, is unclear. Here we use simultaneous sleep staging from scalp EEG with intracranial EEG recordings from medial temporal lobe to investigate how behavioral state modulates the spatial and spectral scales of local field potential synchrony in focal epileptic hippocampus. The local field spectral power and linear correlation between adjacent electrodes provide measures of neuronal population synchrony at different spatial scales, ∼1 and 10 mm, respectively. Our results show increased connectivity inside the SOZ and low connectivity between electrodes in SOZ and outside the SOZ. During slow-wave sleep, we observed decreased connectivity for ripple and fast ripple frequency bands within the SOZ at the 10 mm spatial scale, while the local synchrony remained high at the 1 mm spatial scale. Further study of these phenomena may prove useful for SOZ localization and help understand seizure generation, and the functional deficits seen in epileptic eloquent cortex.
Keywords: epilepsy; lidé; Middle Aged; Adult; Brain Mapping; Sleep; epilepsie temporálního laloku; Female; Epilepsy, Temporal Lobe; Hippocampus; Spectrum Analysis; mozkové vlny; connectivity; Humans; elektroencefalografie; spektrální analýza; Electroencephalography; lidé středního věku; mužské pohlaví; mladý dospělý; ženské pohlaví; Brain Waves; Young Adult; behavioral state; mapování mozku; Male; spánek; hipokampus; intracranial EEG; dospělí; seizure onset zone